Angular-adjustable single-channel narrow-band filter based on one-dimensional photonic crystal heterostructure - Wang, Fang (2022)
In this work, we designed a narrow-band filter based on a one-dimensional photonic crystal heterostructure featuring an angle-adjustable single-channel. The design presented here is based on a quarter-wave reflector with a mirror defect layer in the middle of the structure. By combining two defective one-dimensional photonic crystals (PCs), we obtained a heterostructure in which the two sub-PCs had the wavelengths of their defect modes, that is, the same at one incident angle and different at all other incident angles. This structure possessed the single-channel resonant peak in the transmission spectrum under either a normal or an oblique incident angle, and the angle-adjustability was related to the two modifying parameters. The filter based on this heterostructure possessed not only a narrow passband but also a sharp angular pass breadth. These properties have potential applications in angular tunable, single-channel narrow-band filters.